1994
DOI: 10.1007/bf02815411
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of fluorogenic substrates for APP-processing proteases by human brain extracts

Abstract: The proteases that cleave amyloid precursor protein (APP) leading to generation of amyloid A beta peptide are potential targets for therapeutical intervention of Alzheimer disease. We have been pursuing the identification and characterization of these proteases using as probes the fluorogenic substrates encompassing the cleavage sites of APP that we described recently (Wang, G. T., Krafft, G. A. [1992] Bioorg. Med. Chem. Lett. 2, 1665). This article describes results of experiments designed to examine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Increased oxidative stress may further interfere with Ca immobilization, leading to cell death via additional cytotoxic pathways (Esposito et al, 2013; Ong et al, 2013). It has been previously reported that Ca 2+ overload can modulate APP metabolism, and accelerate APP hydrolysis to generate more Aβ (Wang et al, 1994; Ye et al, 2010). Our study and others have shown that Ca increases with age in the brain, and provides further evidence supporting the hypothesis of the imbalance of calcium homeostasis and disturbed Ca flux in the brain can enhance AD progression (Peterson et al, 1985, 1989; Deary and Hendrickson, 1986; Martyn et al, 1989; Kelliher et al, 1999; O’Day and Myre, 2004; Attems et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress may further interfere with Ca immobilization, leading to cell death via additional cytotoxic pathways (Esposito et al, 2013; Ong et al, 2013). It has been previously reported that Ca 2+ overload can modulate APP metabolism, and accelerate APP hydrolysis to generate more Aβ (Wang et al, 1994; Ye et al, 2010). Our study and others have shown that Ca increases with age in the brain, and provides further evidence supporting the hypothesis of the imbalance of calcium homeostasis and disturbed Ca flux in the brain can enhance AD progression (Peterson et al, 1985, 1989; Deary and Hendrickson, 1986; Martyn et al, 1989; Kelliher et al, 1999; O’Day and Myre, 2004; Attems et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The pioneering work on synthetic probes using resonance energy transfer for measurement of hydrolase activity was done in 1972 by Latt et al [91] and was followed by Wang et al [92], significantly improving the donor-acceptor pair from TryptophanDansyl to the nowadays well known EDANS-DABCYL pair. They focused initially on retroviral proteases that are useful in rapid detection of HIV virus protease activity [93] and later on the synthesis of fluorogenic substrates resembling part of the normal and altered amyloid precursor protein, in an attempt to discover the proteases responsible for this lethal "molecular switch" in Alzheimer's disease [94].…”
Section: Cleavable Linkermentioning
confidence: 99%